2010
DOI: 10.1016/j.cma.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive element-free Galerkin method applied to the limit analysis of plates

Abstract: The implementation of an h-adaptive Element-Free Galerkin (EFG) method in the framework of limit analysis is described. The naturally conforming property of meshfree approximations (with no nodal connectivity required) facilitates the implementation of h-adaptivity. Nodes may be moved, discarded or introduced without the need for complex manipulation of the data structures involved. With the use of the Taylor expansion technique, the error in the computed displacement field and its derivatives can be estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 41 publications
0
20
1
Order By: Relevance
“…For the Kirchhoff plates, we can list the works by Christiansen and Larsen [28], Turco and Caracciolo [29], Corradi and Vena [30], Corradi and Panzeri [31], Tran et al [32], Le et al [33][34][35], and Zhou et al [36]. For the Mindlin plates, we can list the works by Capsoni and Corradi [37] and Capsoni and Vicente da Silva [38].…”
mentioning
confidence: 99%
“…For the Kirchhoff plates, we can list the works by Christiansen and Larsen [28], Turco and Caracciolo [29], Corradi and Vena [30], Corradi and Panzeri [31], Tran et al [32], Le et al [33][34][35], and Zhou et al [36]. For the Mindlin plates, we can list the works by Capsoni and Corradi [37] and Capsoni and Vicente da Silva [38].…”
mentioning
confidence: 99%
“…in which˙ e C is determined by Equation (16). In the following, we will show that when triangular elements are used (linear shape functions), CS-FEM and FEM are equivalent, D SF EM ≡ D F EM , regardless the number of SCs.…”
Section: Cs-fem Discretization Of Kinematic Formulationmentioning
confidence: 92%
“…It is known as the stabilized conforming nodal integration (SCNI) scheme. The SCNI scheme has been applied successfully to various problems, for instance, elastic analysis [12][13][14], plastic limit analysis [15], error estimation [16] and a stabilized mesh-free equilibrium model for limit analysis [17]. It is shown that, when the SCNI scheme is applied, the solutions obtained are accurate and stable, and locking problems can also be prevented.…”
Section: Introductionmentioning
confidence: 99%
“…In the regions where error exceeds the pre-de ned tolerance, new nodes are added at the vertices of the cell. It is noteworthy that based on the numerical tests performed by Le et al [16], the optimum value of pre-de ned local error tolerance is selected as 0.001. The restructuring process continues until the error tolerance is satis ed at all nodes.…”
Section: Example (1): Smooth Strip Footing Resting On Purely Cohesivementioning
confidence: 99%
“…This adaptive procedure has been proposed for the nite-element limit analysis [10][11][12][13][14][15] as well as the mesh-free limit analysis [16] approaches. The main policy in these methods is de ning a posteriori error estimator and establishing an adaptive re nement strategy based on the reduction of this error.…”
Section: Introductionmentioning
confidence: 99%